HAMBATAN INTERNASIONALISASI TERHADAP PENGEMBANGAN OBYEK WISATA RUPAT UTARA SEBAGAI WISATA INTERNASIONAL 2018-2022 - Fani Dwi Putri Octavia; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT North Rupat is one of the mainstay coastal marine tourism objects of Bengkalis Regency tourism and is one of the national tourism strategic areas, this study aims to determine cultural diplomacy efforts and implementation of tourism development carried out by the Riau Provincial Tourism Office in Promoting North Rupat Tourism Objects, Bengkalis Regency to become an international tourism destination. This research uses qualitative methods, with data collection techniques through primary data collection sourced from field research and through secondary data collection through literature studies sourced from several books, journals, articles, websites and using the concept of Tourism Development and Diplomacy Theory in Cultural Diplomacy. The result of this paper is that the Riau Provincial Tourism Office has a strategy for the process of promoting international tourism destinations, namely Paid Media (P), Owned Media (O), Social Media (S), Endorser (E) Endorser or KOL, and pre-event, on-event, and post-event. The use of Cultural Diplomacy theory in an effort to internationalize North Rupat tourism objects into international tourism destinations by the Department of Tourism, Culture, Youth and Sports accompanied by the Association of The Indonesian Tours And Travel Agencies (ASITA) Riau. As well as using benchmarks on the main elements of tourism development as a medium to analyze who North Rupat tourism objects become international tourism. Keywords: Tourism Office of Riau Province, ASITA RIAU, Tourism Development, Tourism Promotion, Cultural Diplomacy